Arthrofibrosis After Total Knee Arthroplasty Managed with Manipulation Under Anesthesia - Jajou, Lawrence; Scuderi, Giles R. (The Journal of Knee Surgery, 2026)
Arthrofibrosis after total knee arthroplasty (TKA) is the result of excessive scar formation because of the inflammatory insult of surgery. This formation can lead to significant loss of range of motion, pain, and functional deficits requiring further treatment. Although much has been researched on arthrofibrosis, it continues to lack definitive diagnostic testing. This has led to an array of approaches and treatments to relieve patients of this complication. In response to the inflammatory insult caused by TKA, arthrofibrosis occurs because of an overactivation and proliferation of myofibroblasts. This leads to an abundant deposition of type I collagen and scar tissue formation. This general cascade has been found to be associated with multiple signaling pathways involving primarily transforming growth factor-beta. Additionally, there is a multifactorial component of risk factors and comorbidities, which contribute to the formation of arthrofibrosis. Arthrofibrosis is diagnosed as both a clinical diagnosis and a diagnosis of exclusion. Using the patient's history, clinical examination, and diagnostic testing to rule out other etiologies, one can obtain the diagnosis of arthrofibrosis. While stiffness is an umbrella term that is commonly used interchangeably with arthrofibrosis, it is imperative to use the diagnostic testing to systematically rule out other causes of stiffness. There is no definitive imaging, biopsy, or biomarker test specific for arthrofibrosis currently, which makes obtaining a definitive diagnosis difficult. Nonoperative and operative treatment options are available for the treatment of arthrofibrosis. Most conservative approaches begin with physical therapy, appropriate pain management, and oral anti-inflammatory medication. Treatment options rise in invasiveness with manipulation under anesthesia, arthroscopic lysis of adhesions, open lysis of adhesions, and ultimately revision TKA. This review will focus on the role of manipulation under anesthesia in the setting of arthrofibrosis.
Keywords: total knee; arthrofibrosis; stiffness; manipulation